PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR AKUNTANSI BIAYA - Wakijo Wakijo; Pargito Pargito; Eddy Purnomo (Faculty of Teacher Training and Education, University of Lampung, 2013)
This research which purposed to find the model and to know effectivinnes of the through the implementation of inquiry in improving activities and their learning result based Intruction with specific topic base price process method subject of the research. The method which used is Classroom Action Research. The result of this research shows that first is learning activity from the first cycle to the second cycle has the improvement up was from 61,02% in the first cycle up to 66,67% in the second cycle. Where as from the second cycle to the third cycle has improvement up was from 66,67% in the second cycle up to 83,33% in the third cycle. The second is the result of students’ learning has the improvement between the first cycle to the second cycle was from 58,33% in the first cycle up to 77,78% in the second cycle. In the second cycle to the third cycle has the improvement up was from 77,78% in the first cycle up to 94,44% in the third cycle.Penelitian ini bertujuan untuk menemukan model dan mengetahui efektifitas strategi pembelajaran inkuiri dalam meningkatkan aktivitas dan hasil belajar mata kuliah akuntansi biaya. Metode yang digunakan adalah PTK. Hasil penelitian ini menunjukkan bahwa aktivitas belajar dari siklus pertama ke siklus kedua mengalami peningkatan dari 61,02% pada siklus pertama menjadi 66,67% pada siklus kedua. Siklus kedua ke siklus ketiga mengalami peningkatan sebesar 66,67% pada siklus kedua menjadi 83,33% pada siklus yang ketiga. Hasil belajar mahasiswa mengalami peningkatan antara siklus satu ke siklus dua yaitu sebesar 58,33% pada siklus yang pertama menjadi 77,78% pada siklus yang ke dua, siklus dua ke siklus tiga dari 77,78% siklus yang ke dua menjadi 94,44% pada siklus yang ke tiga.Kata kunci: aktivitas, hasil belajar, strategi pembelajaran inkuiri